دور المراجع الخارجي في الحد من اساليب المحاسبة الابداعية: بالتطبيق على ديوان المحاسبة فرع المنطقة الغربية - عبداللطيف الهادي امحمد احمد (Surman Journal of Science and Technology, 2025)
This study aims to identify the role of the external auditor in reducing creative accounting practices, with an applied focus on the Audit Bureau – Western Region Branch. Using the descriptive-analytical method, the research examines how audit standards, independence, professional competence, and ethics contribute to detecting and limiting creative accounting practices in income statements and balance sheets. The findings revealed a strong inverse relationship between audit quality and the spread of creative accounting. Auditor independence, integrity, and technical expertise were found to be essential factors in enhancing the credibility of financial reporting. The study also showed that effective audit planning, evaluation of internal control systems, and adherence to international auditing standards significantly contribute to detecting manipulative financial practices. Furthermore, legal accountability and continuous professional training strengthen auditors’ effectiveness in reducing unethical accounting behavior. The study concludes that enhancing audit quality and reinforcing the independent role of the external auditor are crucial steps toward achieving transparency, reliability, and public confidence in financial statements.